Kesesuaian Materi Teknik Pemesinan SMK Dengan Kualifikasi Kerja Industri Pemesinan - Harahap, Rasyid Ridho; Yolana Nursafti; Dahrul Aman Harahap (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study aims to identify the level of relevance between the vocational materials taught in vocational schools and the job qualifications required in the machining industry, using normative standards as a reference. Based on data from production operator tasks obtained through direct observation at PT. Sawit Riau Makmur, and materials taken from vocational school education documents based on the Merdeka Curriculum, the results of the study show that the relevance of vocational materials in vocational schools to the tasks of operators in the industry is still low. Only 1.59% of the material is relevant to industrial tasks, while most of the material is either inappropriate or does not cover the industry's needs. This highlights a competency gap that needs to be addressed immediately through curriculum revision. Errors in the preparation of this curriculum impact the readiness of vocational school graduates to work directly in the industry.